Oral Surgery in Patients Taking Direct Oral Anticoagulants (DOACs): A Practical Review of the Literature - Lupi, Saturnino Marco; Farahani, Mohammad Reza Dermenaki; Ronza, Elisa Di; Cerri, Michael; Baena, Arianna Rodriguez y; Baena, Ruggero Rodriguez y (The Journal of Dentists, 2019)
Recently, four new oral anticoagulant – dabigatran etexilate (direct thrombin inhibitor) and rivaroxaban, apixaban and edoxaban (Xa factor direct inhibitor) – have been approved for the prevention of venous thrombosis and cardiovascular events. As the number of patients taking these drugs is increasing, it is important that the dentist is familiar with these new oral anticoagulants, their indications, methods of action and in particular the management of the patients undergoing oral surgery. This literature review is conducted to highlight the medical uses of these new oral anticoagulants and their pharmacologic properties, the clinical condition of the patient that may influence the choice to discontinue the DOAC and peri-operative management of the patient. Collaboration with the attending physician is crucial.